Global systematic review of the effects of suicide prevention interventions in Indigenous peoples. Issue 12 (11th August 2020) - Leske, Stuart; Paul, Elise; Gibson, Mandy; Little, Brock; Wenitong, Mark; Kolves, Kairi
Abstract : Objective: Suicide rates are often higher in Indigenous than in non-Indigenous peoples. This systematic review assessed the effects of suicide prevention interventions on suicide-related outcomes in Indigenous populations worldwide. Methods: We searched CINAHL, Embase, PubMed, PsycINFO, ProQuest Dissertations & Theses and Web of Science from database inception to April 2020. Eligible were English language, empirical and peer-reviewed studies presenting original data assessing the primary outcomes of suicides and suicide attempts and secondary outcomes of suicidal ideation, intentional self-harm, suicide or intentional self-harm risk, composite measures of suicidality or reasons for life in experimental and quasi-experimental interventions with Indigenous populations worldwide. We assessed the risk of bias with the Cochrane Risk of Bias Tool and the Risk of Bias Assessment for Non-randomised Studies. Findings: We included 24 studies from Australia, Canada, New Zealand and the USA, comprising 14 before–after studies, 4 randomised controlled trials (RCTs), 3 non-randomised controlled trials, 2 interrupted time-series designs and 1 cohort study. Suicides decreased in four and suicide attempts in six before–after studies. No studies had a low risk of bias. There was insufficient evidence to confirm the effectiveness of any one suicide prevention intervention due to shortage of studies, risk of bias, and population and intervention heterogeneity. Review limitations include language bias, no grey literature search and data availability bias. Conclusion: For the primary outcomes of suicides and suicide attempts, the limited available evidence supports multilevel, multicomponent interventions. However, there are limited RCTs and controlled studies.